"You have to be resilient": Producer perspectives to navigating a changing agricultural system in California, USA. (April 2023) - Quandt, Amy
Abstract: CONTEXT: Imperial Valley, California is called 'America's winter salad bowl' as the agricultural sector produces 2/3 of the winter vegetables eaten in the U.S. However, there is little understanding of the interplay of policy, environmental conditions, and economic components of the agricultural system producers face in the valley. OBJECTIVE: Using a resilience approach, this study asks the research question of how producers in the Imperial Valley perceive and are adapting to changing conditions. METHODS: Through interviews with eight agricultural producers, this paper identifies current challenges and strategies producers employ to navigate a changing agricultural system and build resilience for the future. RESULTS AND CONCLUSIONS: Results highlight the critical role of government policies in the establishment of agriculture in the Valley, while producers see recent policies, such as labor and food safety regulations, as increasing their operation costs. Producers face economic challenges including losing contracts to Mexico, market price fluctuations, land leasing, and the COVID-19 pandemic. Maintaining access to water resources and investing in mechanization and technological innovations are two strategies producers use to maintain resilience and navigate change. SIGNIFICANCE: Understanding how producers remain resilient given ongoing, and often accelerating, political, environmental, and economic change is critical to maintain agricultural systems in California and beyond. Graphical abstract: Unlabelled Image Highlights: Explores producer perspectives to understand policy, environmental, and economic change within an agricultural system. Government policy has negative and positive impacts on producer resilience, depending on the policy and context. Labor and food safety regulations are major policy drivers of change, increasing operating costs. Producers secure water access and invest in mechanization to build resilience to future change. Understanding how producers navigate change is critical to maintaining agricultural systems.